Eksplorasi Bakteri Endofit dari Akar Tanaman Adam Hawa dan Potensinya sebagai Agens Hayati dan Pemacu Pertumbuhan Tanaman Padi - Ankardiansyah Pandu Pradana; Diana Putri; Abdul Munif (Jurnal Fitopatologi Indonesia, 2015)
Rhoeo discolor has been known to have a good adaptation to various environmental conditions. This character might be due to mutualistic association with endophytic bacteria. The objective of this study was to isolate endophytic bacteria from roots of R. discolor and to evaluate their potency as biocontrol agents and plant growth promoters. The methods to isolate endophytic bacteria involved the following methods, sterilization of root surface, grinding of root tissues, dilution, and plating in the medium tryptone soya agar (TSA). A total of 21 isolates of endophytic bacteria were isolated from the roots of R. discolor. Based on hypersensitivity test on tobacco leaves, 19 isolates showed negative reaction (no necrosis symptom) and only 2 isolates showed positive reaction (necrosis was developed). The results on biocontrol and growth promoters assay showed that 7 isolates were able to inhibit the growth of Fusarium oxysporum under in vitro test and 12 isolates were able to increase the growth of rice seedlings.